Apoptosis through Death Receptors in Temporal Lobe Epilepsy-Associated Hippocampal Sclerosis - Marcelo Ananias Teocchi; Lília D’Souza-Li (Mediators of Inflammation)
Seizure models have demonstrated that neuroinflammation and neurodegeneration are preponderant characteristics of epilepsy. Considering the lack of clinical studies, our aim is to investigate the extrinsic pathway of apoptosis in pharmacoresistant temporal lobe epilepsy (TLE) associated with hippocampal sclerosis (HS) patients, TLE(HS). By a specific death receptor-mediated apoptosis array plate, 31 upregulated targets were revealed in the sclerotic hippocampus from TLE(HS) patients. Amongst them are the encoding genes for ligands (FASLG, TNF, and TNFSF10) and death receptors (FAS, TNFRSF1A, TNFRSF10A, and TNFRSF10B). In addition, we evaluated the hippocampal relative mRNA expression of the two TNF receptors, TNFRSF1A and TNFRSF1B, in patients, being both upregulated (n=14; P<0.01 and P<0.04, resp.) when compared to the post mortem control group (n=4). Our results have clearly suggested that three different death receptor apoptotic systems may be associated with the maintenance and progression of TLE-associated HS: (1) TNF-TNFRSF1A, (2) FASLG-FAS, and (3) TNFSF10-TNFRSF10A/B. Their effects on epilepsy are still scarcely comprehended. Our study points out to TNF and TNF receptor superfamily pathways as important targets for pharmacological studies regarding the benefits of an anti-inflammatory therapy in these patients.